Legal Protection for Journalists Regarding Freedom of Expression - Maria Febriansi Dwiasri Harung; Alysia Zabina; Soni Esrayanus Benu; Muhammad Dito Zakharia (Mimbar Keadilan, 2026)
Indonesia is a country that upholds the principles of human rights as enshrined in its constitution and various national and international legal instruments that have been ratified. One of the most fundamental human rights is freedom of expression, which includes the freedom to express thoughts verbally, in writing, or through other media. This freedom is closely related to the profession of journalism, which plays a strategic role in conveying information objectively and accurately to the public. In carrying out their duties, journalists often face various challenges, including pressure, intimidation, and criminalization, which can threaten press freedom. Therefore, legal protection for journalists is an important aspect in guaranteeing freedom of expression in Indonesia. Law No. 40 of 1999 on the Press serves as the legal basis for guaranteeing press freedom and providing protection for journalists in carrying out their profession. This study focuses on a normative analysis of these laws and regulations to examine the extent to which their legal substance is capable of providing real protection for journalists' rights. Using a normative legal approach, this study evaluates the effectiveness of regulations in guaranteeing responsible press freedom and the legal mechanisms available in cases of violations of freedom of expression.